Between Black and White: The Coloring of Asian Americans - Kim D. Chanbonpin (Washington University Global Studies Law Review, 2015)
As in other ethnic and racial groups, colorism plays a significant role in the social interactions in and among Asian Americans. Investigating colorism in the Asian American community provides insights into how group members construct their own racial identities in relation to the broader race-stratified society. A colorism inquiry is a necessary intervention into the existing discourse of Asian American identity construction because it complicates common understandings of the Black/White binary in ways that shed new light on inter- and intra-racial relationships. This article addresses colorism in the Asian American community, and demonstrates both how Asian Americans have been racialized within the Black/White binary as well as how that dichotomy has impacted processes of internal self-identification based on color and skin tone within Asian American communities. Further, this article interrogates the Model Minority Myth. Read within the context of the Black/White binary, the Myth presents a choice for Asian Americans—to either accept or reject invitations to Whiteness. Being attentive to how and where Asian Americans fit into the racial structure of the United States—and how that structure may be reproduced in color hierarchies within the Asian American community—can provide insights into where and how Asian Americans can participate in interracial coalitions for racial justice.
Keywords: Asian American; Model Minority; Race; Colorism